Pengaruh Dana Alokasi Umum, Dana Alokasi Khusus, Dan Pendapatan Asli Daerah Terhadap Pengalokasian Belanja Modal Kabupaten Bungo Tahun 2016 – 2021 - Zikral, Zikral; Kusumastuti, Ratih; Zulma, Gandy Wahyu Maulana (Politeknik Negeri Ambon, 2024)
This study aims to examine the effect of the General Allocation Fund (DAU), Special Allocation Fund (DAK, and Regional Original Revenue (PAD) on Bungo Regency local government capital expenditure allocation for 2016-2021. The subject of this study is the Bungo Regency government, and the object of this study is the General Allocation Fund (DAU), Special Allocation Fund (DAK), Local Original Revenue (PAD), and Capital Expenditure Allocation. The type of data collected is quantitative data sourced from Budget Realization Reports and documents. The method used in this study is the Multiple Linear Regression test. The results showed that the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Regional Original Revenue (PAD) together have a significant effect on the Capital Expenditure Allocation in Bungo Regency. Keywords: general allocation fund, special allocation fund, local original revenue.